Filozofia religii a filozofia edukacji religijnej - Moskal, Piotr (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In this article I discuss the following: 1. Secularization and desecularization and the metaphysics of man and religion; 2. Religion as a way of life; 3. The social aspects of religion and the problem of the neutrality of the outlook on life; 4. The scope of religious education; 5. The proper understanding of the inclusivism of religious education.
Keywords: culture; inclusivism; neutrality of the outlook on life; philosophy of religion; philosophy of religious education; religion; society